An analysis of the use of cloud computing among university lecturers: a case study in Zimbabwe - Musungwini, Samuel; Mugoniwa, Beauty; Furusa, Samuel S.; Rebanowako, Taurai G. (University of the West Indies, 2016)
loud computing is a novel model of computing that may bring extensive benefits to users, institutions, businesses and academics, while at the same time also give rise to new risks and challenges. This study looks at the benefits of using Google docs by researchers and academics and analysing the factors affecting the adoption and use of the technology by Lecturers at a university in Zimbabwe. Interviews were used to get an insight into the issues affecting the adoption and use of this novel technology. The information elicited from interviews helped in the design of the questionnaire that was used to draw out information from the subjects. The findings indicated the knowledge gap and the need to carry out workshops to try and enlighten the Lecturers on the value of this technology.